"Visual arts and visual perception" (Comprehensive Journal of Science, 2025)
This research aims to examine the relationship between visual arts and visual perception as an interactive relationship based on the integration between the visual structure of the artwork and the perceptual process of the receiver. Visual arts organize visual elements such as line, color, mass, and space to create an aesthetic structure open to interpretation, while visual perception plays a key role in receiving, organizing, and interpreting these elements based on cognitive and visual experience. The study adopts the descriptive approach, focusing on related literature and previous studies. The results indicate that the relationship between visual arts and visual perception is complementary, where visual organization guides perception, and perception determines the level of aesthetic appreciation and understanding of the artwork, also showing that differences in visual experience lead to multiple readings of the same artwork.
Keywords: visual arts, visual perception, artistic composition, aesthetic appreciation, visual thinking